2020
DOI: 10.1007/s00604-020-04424-2
|View full text |Cite
|
Sign up to set email alerts
|

Reusable optofluidic point-of-care testing platform with lyophilized specific antibody for fluorescence detection of cholylglycine in serum

Abstract: A reusable optofluidic point-of-care testing platform (OPOCT) was successfully constructed through integrating evanescent wave fluorescence technology into an all-fiber-based optofluidic system. The compact design of the OPOCT allows it to be portable and suitable for on-site sensitive determination of biomarkers in serum without complicated and costly procedures. The sensitivity of 90.9 pM for antibody determination is observed thanks to the high transmission efficiency of excitation light and fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Fluorescent substances mainly include substances with fluorescence effect, such as fluorescein and its derivatives ( Hu et al, 2016 ), rhodamine ( Feng et al, 2002 ), quantum dots (QDs) ( Zhou et al, 2020 ), lanthanide chelates ( Lee et al, 2020 ), essence dyes ( Liu J. et al, 2020 ) and phycoerythrin ( Yang et al, 2020 ), as well as some substances that can emit fluorescence under the action of enzymes, which usually produce visible light after the irradiation of ultraviolet or X-ray. However, the sensitivity of the traditional fluorescein-labeled (fluorescein, etc.)…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…Fluorescent substances mainly include substances with fluorescence effect, such as fluorescein and its derivatives ( Hu et al, 2016 ), rhodamine ( Feng et al, 2002 ), quantum dots (QDs) ( Zhou et al, 2020 ), lanthanide chelates ( Lee et al, 2020 ), essence dyes ( Liu J. et al, 2020 ) and phycoerythrin ( Yang et al, 2020 ), as well as some substances that can emit fluorescence under the action of enzymes, which usually produce visible light after the irradiation of ultraviolet or X-ray. However, the sensitivity of the traditional fluorescein-labeled (fluorescein, etc.)…”
Section: Research Progress Of Immunosensorsmentioning
confidence: 99%
“…One of the few studies on CG’s performance as a biomarker, Tanggo et al, revealed that CG concentration is elevated in patients with acute hepatitis and liver cirrhosis and could be used in screening individuals for cirrhosis ( 62 ). In a 2020 study, Liu et al ., showed that a reusable optofluidic point-of-care testing platform could be successfully adapted for the measurement of CG concentration in serum, with the authors noting that it can offer quick, easy and early diagnosis ( 63 ).…”
Section: Role Of Direct Biomarkers In Hepatic Injurymentioning
confidence: 99%
“…ey integrated evanescent wave fluorescence technology into an all-fiber-based optofluidic system to increase the reusability of the system. Although the LOD was 0.025 μg/ mL which was not enough for diagnostic criteria, the sensitivity could be improved simply by the dilution of the serum sample [110]. Different from the previous attempt to enhance reusability, in 2020, Yang et al developed a low-cost disposable experimental device that could be mass-produced.…”
Section: Optofluidic System In Immunoassaysmentioning
confidence: 99%